2014
DOI: 10.1007/s40653-014-0006-z
|View full text |Cite
|
Sign up to set email alerts
|

Community Violence and Psychological Adjustment in Youth: Role of Emotional-Social Intelligence

Abstract: The current study examined the potential mechanism of emotional-social intelligence in the relation between exposure to community violence (CV) and psychological adjustment in ethnic minority youth. Using responses from 114 low-income youth ages 11 to 15 years old, results indicated that component parts of emotionality (i.e., awareness of one's feelings, recognition of others' feelings, managing negative emotions, and flexible problem-solving) were stronger predictors for youth adjustment (i.e., internalizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
(33 reference statements)
3
6
0
Order By: Relevance
“…Our findings thus contradict previous research that evidenced the role of high emotional intelligence (Asad et al, 2018;Ciarrochi et al, 2002) and high cognitive skills (Riglin et al, 2016;McMahon et al, 2013) in protecting mental health from social adversity, stress and violence. Instead our findings are similar to some studies among African American adolescents exposed to socio-economic adversity and community and gang violence (Day et al, 2005;Stokes and Jackson, 2014), which did not find a protective function of high EI for mental health. Also similarly to ours, the results by Bellair and McNulty (2010) show that high cognitive skills did not protect adolescents'mental health from negative impact of severe poverty, stress and community violence.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our findings thus contradict previous research that evidenced the role of high emotional intelligence (Asad et al, 2018;Ciarrochi et al, 2002) and high cognitive skills (Riglin et al, 2016;McMahon et al, 2013) in protecting mental health from social adversity, stress and violence. Instead our findings are similar to some studies among African American adolescents exposed to socio-economic adversity and community and gang violence (Day et al, 2005;Stokes and Jackson, 2014), which did not find a protective function of high EI for mental health. Also similarly to ours, the results by Bellair and McNulty (2010) show that high cognitive skills did not protect adolescents'mental health from negative impact of severe poverty, stress and community violence.…”
Section: Discussionsupporting
confidence: 91%
“…Also similarly to ours, the results by Bellair and McNulty (2010) show that high cognitive skills did not protect adolescents'mental health from negative impact of severe poverty, stress and community violence. Similar to Stokes and Jackson (2014), our results showed that good cognitive skills were associated with low mental health problems, but only when adolescents were exposed to low level of violence. Severe violent experiences thus neutralized the potential beneficial effect of cognitive resources on mental health.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations